1985
DOI: 10.1007/bf00291067
|View full text |Cite
|
Sign up to set email alerts
|

Reduced transcapillary escape of albumin during acute blood pressure-lowering in Type 1 (insulin-dependent) diabetic patients with nephropathy

Abstract: The effect of acute arterial blood pressure lowering upon albumin extravasation was studied in 10 patients with nephropathy and retinopathy due to long-standing Type 1 (insulin-dependent) diabetes. The following variables were measured: transcapillary escape rate of albumin (initial disappearance of intravenously injected 125I-labelled human serum albumin), and urinary albumin excretion rate (radial immunodiffusion). The study was performed twice within 2 weeks, with the patients receiving an intravenous injec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
13
1
3

Year Published

1988
1988
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 34 publications
0
13
1
3
Order By: Relevance
“…Reduction of hydrostatic pressure in the microcirculation has been suggested as a likely factor. Direct [48] and indirect evidence suggest that capillary hydrostatic pressure is elevated in IDDM patients [47,49], while normal capillary pressure (finger nail fold) has been reported in normotensive NIDDM patients [50]. However, increased capillary pressure has been documented in essential hypertension [51] and hypertension was prominent in our NIDDM patients with (83 %) and without (30 %) diabetic nephropathy.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…Reduction of hydrostatic pressure in the microcirculation has been suggested as a likely factor. Direct [48] and indirect evidence suggest that capillary hydrostatic pressure is elevated in IDDM patients [47,49], while normal capillary pressure (finger nail fold) has been reported in normotensive NIDDM patients [50]. However, increased capillary pressure has been documented in essential hypertension [51] and hypertension was prominent in our NIDDM patients with (83 %) and without (30 %) diabetic nephropathy.…”
Section: Discussionmentioning
confidence: 62%
“…Blood pressure and smoking were associated with the high TER alb in the normoalbuminuric NIDDM patients. Previous studies have demonstrated that systemic blood pressure elevation accelerates TER alb while acute and chronic blood pressure reduction normalize TER alb in both diabetic and non-diabetic subjects [23, [45][46][47]. Reduction of hydrostatic pressure in the microcirculation has been suggested as a likely factor.…”
Section: Discussionmentioning
confidence: 99%
“…Proteinuria is the initial and major symptom of diabetic nephropathy, and is the result of increased glomerular permeability (Parving et al, 1985). The expression of VEGF is increased in the diabetic kidney in association with hyperfiltration, proteinuria, and glomerular hypertrophy (Cooper et al, 1999), and these conditions are suppressed by the blocking of VEGF (de Vriese et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Two mechanisms have been suggested as an explana tion for the increase filtration of albumin in diabetics: hemodynamic changes in the renal microcirculation [9] which have been linked to rheological changes [10] or a loss of fixed negative charges in the glomerular capillary wall [11,12]. However, the relationship between rheologi cal changes and microalbuminuria has been refuted by Hill et al [13].…”
mentioning
confidence: 97%